FLEXURAL BEHAVIOR OF SLURRY INFILTRATED FIBER CONCRETE (SIFCON) CONTAINING SUPPLEMENTARY CEMENTITIOUSE MATERIALS - Ahmed Salih, Shakir; Jwad Frayyeh, Qais; Abed Al-wahab Ali , Manolia (Journal of Engineering and Sustainable Development, 2018)
Slurry Infiltrated fiber Concrete (SIFCON) is a relatively new high performance material and can be considered as a special type of Fiber Reinforced Concrete (FRC) with high fiber content. The matrix consists of flowing mortar or cement slurry which must infiltrate properly through the fiber network placed in molds. SIFCON possessing excellent mechanical properties coupled with large ductility and toughness values. SIFCON has found application in area where high ductility and energy absorption are needed especially in seismic-resistant reinforced concrete frames and in structure under abnormal or explosive loads. Other successful applications include pavement overlays, repair of prestressed beams and repair of structural reinforced concrete element.The main aim of this study is to determine the effect of hooked ended steel fiber content and mineral admixture replacement silica fume (SF) on strength and deformation characteristics of SIFCON specimens under flexural loading. Three volume fraction of steel fiber (6, 8.5, and 11) % were used in this investigation .The percentage of SF replacement was (10%), by weight of cement in SIFCON slurry. Both the flexural strength and toughness characteristic were carried out by testing specimens of 100*100*400 mm at the age of 7and 28 days. The results obtained from these tests were compared with those carried out on conventional fiber reinforced mortar (FRM) with 2% fiber content, as control specimens. The test results show superior characteristics of SIFCON ,as compared with normal FRM ,which were affected in positive manner by using cementitiouse materials (SF) as a partial replacement by weight of cement, and with increasing the volume fraction of steel fiber. The flexural strength and toughness value up to (28.08 MPa ) and (159 N.mm),respectively were obtained at age of 28 days.